THE COMBINED ACTIONS OF CHLORAMPHENICOL AND OF BACTERICIDAL ANTIBODY PLUS COMPLEMENT ON SALMONELLA TYPHOSA - Treffers, Henry P. (The Rockefeller University Press, 1954)
Quantitative determinations, employing turbidimetric growth assays, have been made of the inhibitory actions of choramphenicol, and of specific antibody plus complement, separately, and in combination. In experiments with the Ty2 strain of S. typhosa the combined activities of the two groups of reagents have been predicted, within 3 per cent, from the activities of the separate components, on the hypothesis of joint, independent action (additive inhibitions). A fourfold increase in resistance to chloramphenicol of the 0901 strain of S. typhosa has been shown to have little, if any, effect on its susceptibility to the bactericidal action of anti-O antibody and complement. Indirect evidence indicates that the latter may not be a general effect but may vary with the particular strain.